EFEKTIVITAS TEAM ASSISTED INDIVIDUALIZATION UNTUK MENGURANGI PROKRASTINASI AKADEMIK - Syaiful Indra (Jurnal Edukasi : Jurnal Bimbingan Konseling, 2015)
Academic procrastination understood as maladaptive behavior that can hinder academic success. Guidance and counseling implementation is can contribute to reduce the students academic procrastination. The service is can be optimally, the team assisted individualization of learning models combined in class format. This research uses quantitative methods. This type of study design is a Quasi Experiment with the design of the non-equivalent control group. The population are students MTS Negeri Koto Tangah Padang selected by purposive sampling technique. The instrument used to collect data using a scale, then analyzed using Wilcoxson Signed Ranks Test and Kolmogorov-Smirnov 2 Independent the samples. The findings of this research are, differences significant on academic procrastination the experiment group before and after the learning model technique team assisted individualization, There are differences in the control group on academic procrastination before and after the conventional learning model, and there are differences in the experiment group which given learning model technique team assisted individualization and the control group which given information service, learning model team assisted individualization technique can significantly reduce the students academic procrastination, it was can be used for a variety of problems related with learning activities.